Pengaruh Komposisi Kitosan Terhadap Sifat Fisis Dan Biodegradable Film Komposit Nanoserat Pinang Dengan Castor Oil Sebagai Plasticizer - Ayuzia Puspa Indah; Alimin Mahyudin (Universitas Andalas, 2022)
Research has been carried out on the effect of chitosan composition on the physical and biodegradable properties of areca nut nanofiber composite films with castor oil as a plasticizer. Samples were made using the solution casting method. The variations of chitosan used were 0 g, 0.56 g, 0.7 g, 0.84 g, 1.4 g and one sample used starch with a variation of 0.84 g chitosan. The physical properties of the samples tested were thickness test, FTIR test and FESEM test. Mechanical properties tests include tensile strength, elongation, elasticity, and biodegradation tests. The samples were characterized using a Particle Size Analyzer (PSA) to determine the size of the nanofibers, a Field Emission Scanning Electron Microscope (FESEM) to determine the sample morphology and Fourier Transform Infrared (FTIR) to determine the functional groups. PSA results showed that the nanofibers had a diameter of (79-187) nm. The results of FESEM characterization obtained the shape of a hollow biodegradable plastic surface. The FTIR results indicate the presence of a C=O functional group and C-O is a hydrophilic functional group which indicates that biodegradable plastic is capable of being degraded. The best tensile strength results in the chitosan variation of 0.84 g without starch with a value of 20.04 MPa, the best elongation in the 0.7 g chitosan variation with a value of 138.56%, elasticity 198.66 MPa in the 0.84 g chitosan variation with the addition of starch, the average thickness is 0.25 mm. The higher the variation of chitosan, the thickness, tensile strength, elasticity, and biodegradation of biodegradable plastics increase, while elongation decreases